2022
DOI: 10.3390/biom12121832
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Roles of Post-Translational Modifications of PPARγ in Treating Diabetes

Abstract: The number of patients with type 2 diabetes mellitus (T2DM), which is mainly characterized by insulin resistance and insulin secretion deficiency, has been soaring in recent years. Accompanied by many other metabolic syndromes, such as cardiovascular diseases, T2DM represents a big challenge to public health and economic development. Peroxisome proliferator-activated receptor γ (PPARγ), a ligand-activated nuclear receptor that is critical in regulating glucose and lipid metabolism, has been developed as a powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 89 publications
0
12
0
Order By: Relevance
“…The capacity of H 2 S to regulate glucose uptake and energy metabolism might be harnessed for managing metabolic diseases, such as diabetes [ 107 , 108 ]. Modulating H 2 S levels could improve glucose homeostasis and insulin sensitivity, potentially serving as an adjunct to existing therapies [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The capacity of H 2 S to regulate glucose uptake and energy metabolism might be harnessed for managing metabolic diseases, such as diabetes [ 107 , 108 ]. Modulating H 2 S levels could improve glucose homeostasis and insulin sensitivity, potentially serving as an adjunct to existing therapies [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…H 2 S has gained unprecedented attention as a signaling molecule [ 96 ] in recent years. Its pivotal roles across animals and plants [ 107 , 108 ] in diverse cellular processes have triggered intensive exploration. Divergent as animals and plants may be in terms of physiology, metabolism, and anatomy, their pathways intersect when it comes to hydrogen sulfide’s indispensable roles.…”
Section: Discussionmentioning
confidence: 99%
“…PPARγ is a member of the nuclear hormone receptor family of ligand-inducible transcription factors, which plays a pivotal role in lipid and glucose homeostasis. The activity of PPARγ could be inhibited by CDK5 and MAPK [ 120 ] ( Figure 1 ). It was reported that the activation of PPARγ is involved in upregulating the level of the glucose-dependent insulinotropic polypeptide (GIP) receptor [ 121 ], GLUT4, and pyruvate carboxylase [ 122 , 123 ], which are correlated with insulin sensitization.…”
Section: The Advance Of Applying Vanadium In Ad Treatmentmentioning
confidence: 99%
“…With regard to the former, the bioactivity of PPARγ can be regulated by ligands that bind to peroxisome proliferator response elements (PPREs), the corepressor complex, and the co-activator complex through different domains [14,23]. PPARγ contains four different domains: ligand-independent activation function 1 (AF1), DNA-binding domain (DBD), ligand-binding domain (LBD), and activation function 2 (AF2) [14,24]. PPARγ can bind to PPREs of target genes through its DBD [14].…”
Section: Introductionmentioning
confidence: 99%
“…PTM patterns include acetylation, phosphorylation, ubiquitination, and small ubiquitin-related modifier (SUMOylation). In addition to the mRNA expression of PPARγ, increasing attention has been directed towards these PTMs [24][25][26][27]. In this review, we summarize the normal function versus dysfunction of ECs, with an emphasis on regulatory compounds and PTMs of PPARγ.…”
Section: Introductionmentioning
confidence: 99%